2012
DOI: 10.1534/genetics.112.142554
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Genetic Effects for Survival in Domestic Chickens (Gallus gallus) Are Magnified in Crossbred Genotypes and Show a Parent-of-Origin Effect

Abstract: Through social interactions, individuals can affect one another's phenotype. The heritable effect of an individual on the phenotype of a conspecific is known as an indirect genetic effect (IGE). Although IGEs can have a substantial impact on heritable variation and response to selection, little is known about the genetic architecture of traits affected by IGEs. We studied IGEs for survival in domestic chickens (Gallus gallus), using data on two purebred lines and their reciprocal cross. Birds were kept in grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 59 publications
5
67
0
1
Order By: Relevance
“…In A. thaliana, in contrast, Mutic and Wolf (2007) found positive pleiotropic direct and indirect effects on size-, development-and fitness-related traits. Results of Peeters et al (2012) in laying hens suggest that non-additive effects may have substantial impact on the direct-indirect genetic correlation. They found moderately to strongly negative direct-indirect genetic correlations in crossbred individuals, whereas the correlation was near zero in the purebred parental lines.…”
Section: Genetic Architecture and Sustainability Of Response To Selecmentioning
confidence: 99%
See 3 more Smart Citations
“…In A. thaliana, in contrast, Mutic and Wolf (2007) found positive pleiotropic direct and indirect effects on size-, development-and fitness-related traits. Results of Peeters et al (2012) in laying hens suggest that non-additive effects may have substantial impact on the direct-indirect genetic correlation. They found moderately to strongly negative direct-indirect genetic correlations in crossbred individuals, whereas the correlation was near zero in the purebred parental lines.…”
Section: Genetic Architecture and Sustainability Of Response To Selecmentioning
confidence: 99%
“…In cannibalistic laying hens, for example, the IGE of an individual on the survival probability of its group mates relates to its pecking behaviour. Nevertheless, the variance-component model allows quantifying IGEs solely from survival data and knowledge of which individuals interact with each other (that is., cage composition), without any information on pecking behaviour of individuals (Peeters et al, 2012). The trait-based model, by contrast, requires the inclusion of all traits that functionally underlie the IGE on the focal trait.…”
Section: Modelling Igesmentioning
confidence: 99%
See 2 more Smart Citations
“…Schmidt et al (2006) reported that selection for increased LBW in broiler breeders includes maternal effects which have positive association with the LBW of its progenies after hatch. In addition, Peeters et al (2012) stated that individuals can affect one another's phenotype. The heritable effect of an individual on the phenotype of a conspecific individual is known as an indirect genetic effect (IGE).…”
Section: Discussionmentioning
confidence: 99%